Implicit Contracts, Incentive Compatibility, and Involuntary Unemployment: Thirty Years On - W. Bentley MacLeod; James Malcomson (Institute of Labor Economics (IZA), 2023)
"Implicit Contracts, incentive compatibility, and involuntary unemployment" (MacLeod and Malcomson, 1989) remains our most highly cited work. We briefly review the development of this paper and of our subsequent related work, and conclude with reflections on the future of relational contract theory and practice.
Keywords: D21; D23; D82; D86; L14; L22; L23; L24; 330; relational contracts; informal enforcement; legal enforcement; incentives; private information